The Scaling of Star Formation: from Molecular Clouds to Galaxies. Issue Volume 10:Issue S309(2014) (9th February 2015) - Calzetti, Daniela
Abstract: This is a review of the extant literature and recent work on the scaling relation(s) that link the gas content of galaxies to the measured star formation rates. A diverse array of observing techniques and underlying physical assumptions characterize the determination of these relations at different scales, that range from the tens of parsec sizes of molecular clouds to the tens of kpc sizes of whole galaxies. Different techniques and measurements, and a variety of strategies, have been used by many authors to compare the scaling relations, both within and across galaxies. Although the picture is far from final, the past decade has seen tremendous progress in this field, and more progress is expected over the next several years.